Integrated nutrient management for upland rice - Ranjini P R (Department of Agronomy, College of Agriculture, 2002)
An experiment entitled "Integrated nutrient management for upland rice" was conducted during the first crop season of 2001 at the Instructional Farm, College of Agriculture, Vellayani. The experiment was laid out in RBD with twelve treatments and three replications. The treatments included three levels of nitrogen (60, 75, 90 kg ha'), two levels of substitution (25 and 50 per cent) and two sources of organic manure (farm yard manure and verrnicornpost) The treatments exerted significant influence on most of the biometric and yield attributing characters of upland rice. Application of 90 kg N with 25 per cent substitution through vermicompost along with 45 kg K20 significantly increased the biometric and yield attributes. The treatments influenced the grain protein content, relative leaf water content and nutrient uptake significantly. The highest uptake of nitrogen and potassium was registered when 90 kg N was applied with 25 per cent substitution through vermicompost whereas maximum phosphorus uptake was obtained upon application of 90 kg N with 50 per cent substitution through vermicompost. The soil physical properties were improved due to organic manures. Maximum lowering of bulk density and increase in porosity and water holding capacity were obtained due to the application of 90 kg N with 50 per cent substitution through farmyard manure. There was significant increase in the level of available nutrients and organic carbon in the soil after the experiment. Soil available nitrogen and potassium were highest for the treatment in which 50 per